International organizations and the fight for accountability : the remedies and reparations gap - Ferstman, Carla, 1968- (Oxford : Oxford University Press, 2017)
This title analyses the challenges citizens face obtaining remedies and reparation for harm suffered as a result of the actions of international organisations. It encourages reflection on additional measures to strengthen accountability.
This edition previously issued in print: 2017.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on August 21, 2017).
Keywords: Social responsibility of business; Corporate governance; Globalization -- Social aspects; Business and Management; Business & Management